Efficient Capture of Organic Dyes and Crystallographic Snapshots by a Highly Crystalline Amino‐Acid‐Derived Metal–Organic Framework. Issue 67 (27th November 2018) - Mon, Marta; Bruno, Rosaria; Tiburcio, Estefanía; Casteran, Pierre‐Edouard; Ferrando‐Soria, Jesús; Armentano, Donatella; Pardo, Emilio
Abstract: Invited for the cover of this issue are the groups of Emilio Pardo at Universitat de València, and Donatella Armentano at Università della Calabria. The image depicts both water contamination by industry and decontamination by metal–organic frameworks. Read the full text of the article at 10.1002/chem.201803547 . Abstract : " The high crystallinity of these materials allows for a direct visualization of the mechanisms governing the host–guest interactions ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 17712 ff. (DOI:10.1002/chem.201803547 ).